Efectividad de la Estrategia educativa “Camaleón Sonriente Cuida Tus dientes” en Niños de 5 a 13 años de la Institución Educativa Obando (2022)
The oral health problem in Colombia is generated by factors such as inadequate hygiene, lack of adoption of oral hygiene habits, sugar consumption, among others, which especially affect children; the objective of this study is to determine the effectiveness of the educational st rategy "Camaleón sonriente cuida tus dientes" in children from 6 to 12 years of age at the Obando Educational Institution, for which an longitudinal study was used as a method based on a survey that measures before and after its application; The results ind icated statistically significant differences in variables of knowledge about the use of the toothbrush to remove food debris (p=0.00), variables of attitudes where the dentist is an actor in the teaching process (p=0.006); the study concludes that in more significant improvements. than 70% of the variables there were no